Regular practice of competitive sports does not impair sleep in adolescents: DADOS study - Reyes Beltran-Valls, M.; Garcia Artero, E.; Capdevila-Seder, A.; Legaz-Arrese, A.; Adelantado-Renau, M.; Moliner-Urdiales, D. (Pediatric Exercise Science, 2018)
To analyze differences in sleep quality and duration by athletic status and sex, and to examine the association between physical activity (PA) recommendation and sleep in adolescents. Methods: A total of 267 adolescents [13.9 (0.3) y] from Deporte, ADOlescencia y Salud (DADOS) study (129 girls) were included in this cross-sectional analysis. Athletes competed regularly in organized sport events and trained =3 days per week, but nonathletes did not compete. PA was assessed by GENEActiv accelerometer. PA values were dichotomized into inactive (<60 min/d of moderate and vigorous PA) and active (=60 min/d of moderate and vigorous PA). Sleep quality was evaluated with the Spanish version of the Pittsburgh Sleep Quality Index. Pittsburgh Sleep Quality Index values were dichotomized into >5 (poor quality) or =5 (good quality). Sleep duration was objectively measured by accelerometer. Results: Sleep quality and duration were not statistically different between athletes [median (Mdn) = 4.0, interquartile range (IQR) = 3.0-6.0 and Mdn = 8.0, IQR = 7.4-8.6 h, respectively] and nonathletes (Mdn = 5.0, IQR = 3.0-7.0 and Mdn = 7.9; IQR = 7.3-8.6 h, respectively), P > .05. Nonathlete or inactive adolescents did not show higher risk for poor sleep quality or short sleep duration than athletes [odds ratio (OR) = 1.17; 95% confidence interval (CI), 0.68-2.00 and OR = 0.93; 95% CI, 0.56-1.55, respectively] or active peers (OR = 1.39; 95% CI, 0.66-2.89 and OR = 1.62; 95% CI, 0.78-3.37, respectively). Conclusions: In our group of adolescents, competitive sport practice did not alter sleep patterns. PA recommendations for adolescents may not discriminate between good and poor sleepers.In our group of adolescents, competitive sport practice did not alter sleep patterns. PA recommendations for adolescents may not discriminate between good and poor sleepers.